2006
DOI: 10.1080/01926230601047808
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Profiles in Rats Treated with Tumorigenic and Nontumorigenic Triazole Conazole Fungicides: Propiconazole, Triadimefon, and Myclobutanil

Abstract: Conazoles are a class of azole based fungicides used in agriculture and as pharmaceutical products. They have a common mode of antifungal action through inhibition of ergosterol biosynthesis. Some members of this class have been shown to be hepatotoxic and will induce mouse hepatocellular tumors and/or rat thyroid follicular cell tumors. The particular mode of toxic and tumorigenic action for these compounds is not known, however it has been proposed that triadimefon-induced rat thyroid tumors arise through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 41 publications
1
60
0
2
Order By: Relevance
“…The triadimefon-induced rat thyroid tumors were proposed to arise secondary to hepatic metabolism of T4 with an associated persistent increase in TSH. However, the data from Wolf et al (2006) suggested that although there was induction of UGT enzyme activity and a mild decrease in serum T3 and T4 levels, there were no associated increases in TSH levels. Thus triadimefon-induced thyroid tumors are likely due to another mode of action.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The triadimefon-induced rat thyroid tumors were proposed to arise secondary to hepatic metabolism of T4 with an associated persistent increase in TSH. However, the data from Wolf et al (2006) suggested that although there was induction of UGT enzyme activity and a mild decrease in serum T3 and T4 levels, there were no associated increases in TSH levels. Thus triadimefon-induced thyroid tumors are likely due to another mode of action.…”
Section: Discussionmentioning
confidence: 97%
“…Inflammation responses and damaged proteins could be a source of toxicity in and of itself or could certainly amplify any initial hepatic toxicity. Combining the evidence presented in Wolf et al (2006) with the present systematic analysis of transcription after conazole exposure provides a differential response by triadimefon, associated with dysregulation of cell-regulating processes whereas propiconazole appeared to have a unique toxicity profile of acute inflammation and protein metabolism. Both of these profiles certainly could underlie the observed hepatic toxicity of hypertrophy and increased liver weight, and could serve as key events to characterize and distinguish the rat tumorigen, triadimefon, from nonthyroid tumorigen propiconazole.…”
Section: Pathways Unique To Triadimefonmentioning
confidence: 98%
See 1 more Smart Citation
“…Triazole๊ณ„ ๋†์•ฝ์€ ergosterol biosynthesis inhibitor (EBI)๊ณ„ ๋†์•ฝ์˜ ํ•œ ์ข…๋ฅ˜๋กœ ์นจํˆฌ ์ดํ–‰์„ฑ, ๋‚ด์šฐ์„ฑ ๋†์•ฝ์œผ๋กœ ์˜ˆ๋ฐฉ ๋ฐ ์น˜๋ฃŒํšจ๊ณผ๊ฐ€ ์ข‹์•„ ์‚ฌ์šฉ๋Ÿ‰์ด ๋งŽ ๋‹ค 2) . EBI๊ณ„ ๋†์•ฝ์€ isoprenoid ์ƒํ•ฉ์„ฑ ๊ฒฝ๋กœ์— ๊ด€์—ฌํ•˜์—ฌ ๋ณ‘ ์›์„ฑ ๋ฏธ์ƒ๋ฌผ์˜ ์„ธํฌ๋ง‰ ergosterol ์ƒํ•ฉ์„ฑ์„ ์ €ํ•ดํ•˜์—ฌ ๋ณ‘์› ๊ท  ์ฆ์‹์„ ์ €ํ•ดํ•œ๋‹ค 3) . Triazole๊ณ„ ์ž”๋ฅ˜๋†์•ฝ ๋ถ„์„์— ํ”ํžˆ ์ด ์šฉ๋˜๋Š” ๋ฐฉ๋ฒ•์€ ECD (electron capture detector) 4,5) ๋‚˜ NPD (nitrogen phosphorous detector) 6,7) ๋ฅผ ์ด์šฉํ•œ GC ๋ถ„์„๊ณผ SIM (selective ion monitoring)์ด๋‚˜ Full scan mode์—์„œ์˜ GC-MS .…”
unclassified
“…Many studies have been carried out concerning these pesticides effects in animals. Tumorigenic effects [4], endocrine disrupting effects [5] and disturbances in reproductive systems have been shown in rats [6]. Those fungicides can also induce some tumors in mice livers [7].…”
Section: Introductionmentioning
confidence: 99%